2016
DOI: 10.1523/jneurosci.3578-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Monkey Prefrontal Neurons Reflect Logical Operations for Cognitive Control in a Variant of the AX Continuous Performance Task (AX-CPT)

Abstract: Cognitive control is the ability to modify the behavioral response to a stimulus based on internal representations of goals or rules. We sought to characterize neural mechanisms in prefrontal cortex associated with cognitive control in a context that would maximize the potential for future translational relevance to human neuropsychiatric disease. To that end, we trained monkeys to perform a dot-pattern variant of the AX continuous performance task that is used to measure cognitive control impairment in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 41 publications
3
59
0
Order By: Relevance
“…3A,E). Moreover, at the population level, a decoding approach (Blackman et al, 2016, their Fig. 7A,B) showed that cue information gradually decayed during the delay period.…”
Section: Review Of Blackman Et Almentioning
confidence: 97%
See 4 more Smart Citations
“…3A,E). Moreover, at the population level, a decoding approach (Blackman et al, 2016, their Fig. 7A,B) showed that cue information gradually decayed during the delay period.…”
Section: Review Of Blackman Et Almentioning
confidence: 97%
“…Second, instead of delay neurons, Blackman et al (2016) found many cueselective neurons that responded either in the cue or in the probe period. In B-cue trials, activity in these neurons increased when the cue was presented, whereas in A-cue trials, activity increased in the probe period.…”
Section: Review Of Blackman Et Almentioning
confidence: 99%
See 3 more Smart Citations